L2/L3 equipment deployment scheme in PTN network architecture - Xu DENG (Dianxin kexue)
Relying on technological superiority,packet transport network（PTN）technology has become the main force in the construction of the transport network.In the early PTN network architecture,the L2/L3 equipment was deployed in the core layer.Therefore,it will face two challenges of poor security and low network performance.Based on China Mobile’s current network,the new PTN architecture which L2/L3 equipment deployed in the convergence layer was proposed,and compared the network security and load capacity with L2/L3 equipment deployment in different level.The result shows that the new PTN architecture is better in terms of network security and efficiency.